2019
DOI: 10.1016/j.bpj.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Universal Kinetics of the Onset of Cell Spreading on Substrates of Different Stiffness

Abstract: When plated onto substrates, cell morphology and even stem cell differentiation are influenced by the stiffness of their environment. Stiffer substrates give strongly spread (eventually polarized) cells with strong focal adhesions, and stress fibers; very soft substrates give a less developed cytoskeleton, and much lower cell spreading. The kinetics of this process of cell spreading is studied extensively, and important universal relationships are established on how the cell area grows with time. Here we study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…When cultured on the PAA gels, MCF-7 breast cancer cells showed different morphology between the stiffnesses ( Fig 1B ). Immunofluorescent staining of the actin cytoskeleton and DNA ( Fig 1C ) determined that cells had an increase in cytoplasmic and nuclear area at 4 kPa, compared to 500 Pa ( Fig 1D ), consistent with the literature [ 7 ]. Staining of mature focal adhesions (vinculin) also showed a change in the staining pattern ( Fig 1C ).…”
Section: Resultssupporting
confidence: 89%
“…When cultured on the PAA gels, MCF-7 breast cancer cells showed different morphology between the stiffnesses ( Fig 1B ). Immunofluorescent staining of the actin cytoskeleton and DNA ( Fig 1C ) determined that cells had an increase in cytoplasmic and nuclear area at 4 kPa, compared to 500 Pa ( Fig 1D ), consistent with the literature [ 7 ]. Staining of mature focal adhesions (vinculin) also showed a change in the staining pattern ( Fig 1C ).…”
Section: Resultssupporting
confidence: 89%
“…The fully-assembled mechanosensing complex would then positively signal for Rho/Rac signalling and lead to an activation of F-actin polymerisation. An adaptation of the mechanism of Bell et al (39) to account for this behaviour is shown in Fig. 2.…”
Section: Interactions Between Assembled Integrin-mediatedmentioning
confidence: 96%
“…The component proteins of a mechanosensor complex take a characteristic time to be recruited to the membrane sites, depending on a (fast) diffusion time, and a (much slower) binding time. By examining population dynamics of the time at which the cell becomes hemispherical in shape, Bell et al (39) found that a 5 th order power law determined the number of spread cells at a particular early spreading time, suggesting 5 slow thermally-activated steps Figure 2: Sketch of a possible mechanism for the 5-step assembly of a mechanosensing protein complex Bell et al (39). α-actinin is suggested as a possible basis for nearestneighbour interactions between complexes.…”
Section: Interactions Between Assembled Integrin-mediatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell size and morphology are influenced by matrix stiffness. [ 14–16 ] On a stiff surface, cells can adopt robust focal adhesions with an organized cytoskeleton, thereby facilitating a dynamic push and pull, whereas on soft surface, cells fail to develop this contractile network. In addition to cell morphology, stiffness also influences cellular functions such a proliferation [ 17–19 ] and differentiation.…”
Section: Introductionmentioning
confidence: 99%